Abundance of calcareous nannofossils in ODP Hole 122-761C (Table 1) - James J Pospichal; Timothy J Bralower (PANGAEA, 1992)
A biostratigraphically complete (all nannofossil biozones present) Cretaceous/Tertiary boundary was recovered at Site 761 on the Wombat Plateau, northwest Australian margin, during Ocean Drilling Program Leg 122. A quantitative study of calcareous nannofossils on closely spaced samples across the boundary reveals a rapid change in assemblages in a similar fashion to other Cretaceous/Tertiary boundary sites. Nannofossil species were placed into three categories: Tertiary, Cretaceous, and extquotesinglesurvivors extquotesingle. The rapid sequential turnover in these assemblages is as follows: Cretaceous species are abruptly replaced at the boundary by opportunistic survivor species, which in turn are abruptly replaced by newly evolved Tertiary taxa. The uppermost Maestrichtian assemblage is distinctly mid-latitudinal with few Micula murus and rare to few Nephrolithus frequens. The nannofossil assemblage immediately above the boundary is dominated by an abundance bloom of Cyclagelosphaera spp. No Thoracosphaera or Braarudosphaera abundance blooms are present as at many other localities. The change from a survivor- to Tertiary-dominated assemblage is coincident with the CPla/CPlb nannofossil subzonal boundary, which is marked by the simultaneous first occurrence of several species including Cruciplacolithus tenuis and C. primus. The latter is found to first occur below C. tenuis in the most complete Cretaceous/Tertiary sections. A hiatus between Subzones CPla and CPlb is interpreted to explain this discrepancy.
Supplement to: Pospichal, JJ; Bralower, TJ (1992): Calcareous nannofossils across the Cretaceous/Tertiary boundary, Site 761, Northwest Australia margin. In: von Rad, U; Haq, BU; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 122, 735-751, https://doi.org/10.2973/odp.proc.sr.122.187.1992